THIN-LAYER CHROMATOGRAPHY ON REVERSED PHASE IN THE CHARACTERIZATION OF RETENTION BEHAVIOUR, LIPOPHILICITY, AND PHARMACOKINETICS OF CYANOACETAMIDE DERIVATIVES - Apostolov, Suzana; Vastag, Gyöngyi; Matijević, Borko; Đaković-Sekulić, Tatjana; Marinković, Aleksandar (Journal of the Chilean Chemical Society, 2020)
Biological activity of a molecule is closely related to its lipophilicity. This significant parameter was determinedfor a group of potentially bioactive N-(4-phenylmonosubstituted)-2-cyanoacetamides applying thin-layer chromatography on reversed phase (RP-TLC) in mixtures of water and two organic modifiers separately, i-propanol and dioxane. The effect of the chemical structure of derivatives and the influence of the applied organic modifier on their retention were studied. The determined chromatographic retention constants, RM0, and the chromatographic parameter, m, of compounds were correlated with software calculated partition coefficients, log P as the standard measure of lipophilicity and with different pharmacokinetic predictors applying classical linear and multiple regression analysis. By classical linear regression analysis in both water-modifier systems only RM0-log P and m-log P correlations were established (average r, 0.909 and 0.826). All studied relationships were enhanced by molecular descriptors that fulfilled the modified Lipinski’s rule of five. Thereby, the performed multiple regression analysis gave better correlations (for RM0-log P and m-log Paverage r2, 0.994 and 0.993; for RM0-pharmacokinetic parameters and m-pharmacokinetic parameters average r2 0.978 and 0.980). The obtained results indicate that the chromatographic parameters, RM0 and m determined by RP-TLC at given conditions could be used successfully for the description of lipophilicity and the evaluation of pharmacokinetic properties of N-(4-phenylmonosubstituted)-2-cyanoacetamides as potential bioactive molecules.